Prospective analysis of clinical evolution in chronic urticaria: Persistence, remission, recurrence, and pruritus alone (2022)
ABSTRACT: Background: Population and study’s methodology heterogenicity became clinical evolution of chronic spontaneous urticaria (CSU) highly variable. Objective: In a prospective cohort, we evaluated the different pathways of clinical evolution of CSU and identified possible risk factors. Methods: A total of 685 CSU patients (>12 years) were prospectively followed over 5 years. Diagnosis and follow-up of urticaria were based on medical evaluation and photographic records. Remission was defined as at least 6 months without symptoms (hives, angioedema, or pruritus) and medication. The follow-up included at least 2 visits per year, with photographic registration and clinical evaluation. Predefined clinical and paraclinical variables were included in the regression analyses. Results: We identified four clinical evolution pathways; The cumulative prevalence of remission at 5 years was 59.1%, recurrence was 17.1%, persistence was 11.6%, and chronic pruritus without hives or angioedema was 12.2%. The probability of persistence increased with hypothyroidism diagnosis (HR 0.425, 95% CI 0.290–0.621) and each point in the UAS7 (HR 0.931 95% CI 0.918– 0.945). Conclusion: Chronic urticaria has different evolutions. Disease activity and hypothyroidism predict persistence and remission. Recurrence and chronic pruritus phenotypes require further study to evaluate their causality and prognosis.